2020
DOI: 10.1186/s40834-020-00120-x
|View full text |Cite
|
Sign up to set email alerts
|

Perception, pattern of use, partner support and determinants of uptake of family planning methods among women in rural communities in Southeast Nigeria

Abstract: Background: Family planning is a cost-effective strategy for achieving population development. Family planning uptake is low in sub-Saharan Africa, including Nigeria. We assessed the perception, pattern of use, partner support and determinants of uptake of family planning methods among married women of reproductive age in rural communities of Ebonyi state. Methods: This is part of a baseline report of a quasi-experimental study. A total of 484 married women of reproductive age were recruited using multistage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
6
19
0
Order By: Relevance
“…According to this study, women with secondary-level or higher education were more likely to have decision making autonomy on use of contraceptives than those women without formal education. This finding is in line with other studies such as a study conducted at Mizan-Aman, Ethiopia [ 24 ] and Nigeria [ 13 , 42 ]. As a possible justification, education empowers women to be independent and provides them with essential information that can be crucial in determining their reproductive health.…”
Section: Discussionsupporting
confidence: 93%
“…According to this study, women with secondary-level or higher education were more likely to have decision making autonomy on use of contraceptives than those women without formal education. This finding is in line with other studies such as a study conducted at Mizan-Aman, Ethiopia [ 24 ] and Nigeria [ 13 , 42 ]. As a possible justification, education empowers women to be independent and provides them with essential information that can be crucial in determining their reproductive health.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed women who had secondary level and above education were about eleven times more likely to have decision-making power on family planning use than those who cannot write and read; women who had elementary level education were about seven times more likely to have decision-making power on family planning use than those respondents. This article is in line with other articles such as a study conducted at Mizan-Aman, Ethiopia [13], in Nigeria [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Why should we give long-acting family planning methods that can expose our women to diseases?" (FGD RM 38) This study underscores the ndings from a study done in Nigeria which con rmed that men preferred natural methods to modern contraceptives because of believing that they are free from side effects [22].…”
Section: Belief In Natural Methodsmentioning
confidence: 59%
“…"I am a coffee farmer and I need labor to help in this venture, I need many children who will help me to plant and manage the coffee and for this reason, I only support my wife to use short-term family planning methods and not LARCs" (FGD K 5). Families in Africa consider many children as a source of labour as supported by a study done in Nigeria [22] which states that families preferred to have many children to provide labour. This nding is also consolidated in another study done in Ethiopia where many children were preferred as a source of labour for the family [39].…”
Section: Source Of Labour For the Familymentioning
confidence: 99%